Gut microbiome-based medical methodologies for early-stage disease prevention. (April 2017) - Wang, Jing-Zhang; Du, Wen-Tao; Xu, Yan-Li; Cheng, Shu-Zhen; Liu, Zhi-Jun
Abstract: Recent advancements highlight the important role of gut microbiome in human health. However, a variety of endogenous and exogenous factors, such as genes, foods, drugs, environmental pollutions, oxidative stress, etc., may interfere with the gut microbiome in vivo and increase risks of digestive system diseases, cardiovascular diseases, neurological diseases, obesity, diabetes, cancers, and so on. Abundant discoveries listed in this work support that changes in the composition of the gut microbiome may be potentially used as sensitive early-stage diagnostic biomarkers and that the gut microbiome could be a promising therapeutic target for systemic prevention of multiple human diseases. Interestingly, the microbial culturomics revolution makes it possible to identify much more species and several new species in the gut microbiome. Several innovative articles published by Science and Nature in 2016 further put forward the feasibility of these perspectives, lay grounds for establishing standardized human gut microbiome compositions, and are particularly important for monitoring dysbiosis of the gut microbiome and for precisely reshaping a dysfunctional gut microbiome. Hypothetically, keeping and reconstructing an optimized gut microbiome would be essential to prevent the occurrence of various human diseases. Hence, these advancements have impressive clinical implications for predicting abnormal healthy status of human beings and for preventing the initiation of systemic disorders at an early stage. Graphical abstract: Highlights: Dysbiosis of gut microbiome is a common mechanism of multiple human diseases. Gut microbiome could be a sensitive early-stage biomarker for systemic disorders. Gut microbiome could be a promising therapeutic target for disease treatment. Fecal/gut microbiome transplantation is extremely effective in some patients. Precision medication to modify gut microbiome would be essential for human health.